Hormonal chaos: the scientific and social origins of the environmental endocrine hypothesis - Krimsky, Sheldon (Baltimore, 2002)
"In Hormonal Chaos, Sheldon Krimsky traces the emergence of an unorthodox hypothesis that casts new suspicions on a broad range of modern industrial chemicals. At the heart of his story is the "Environmental Endocrine Hypothesis," the assertion that a class of chemicals called "endocrine disruptors" are interfering with the normal functioning of hormones in animals and humans. Krimsky describes how this controversial theory was first elaborated and explores the complex factors that have contributed to its increased legitimacy and continued controversy."